'I am Still a Young Girl if I Want': Relational Personhood and Individual Autonomy in the Trobriand Islands. Issue 1 (March 2015) - Lepani, Katherine; Taylor, John P.; Morgain, Rachel
Abstract In the Trobriand Islands of Papua New Guinea, sexuality is valued as a positive expression of relational personhood, registering the efficacy of consensual and pleasurable practice in producing and maintaining social relations. The power of sexuality to demonstrate individual and collective capacity and potential holds particular salience for unmarried young people. This paper draws on my ethnographic research on culture and HIV in the Trobriands to address perduring questions about the locus of individual autonomy in Melanesian sociality, where relational personhood shapes identity and modes of exchange in the moral economy. I focus on the gendered agency of youth sexuality, including the use of kwaiwaga, or love magic, in exercising and controlling desire. The narrative identities of two young women provide the lens through which questions of agency are explored, revealing how the autonomous mind, nanola, is central to understanding the embodiment of social relations, how the power of love magic transfers agency from one individual to another, and how individual assertions and acts are ultimately expressions of situated relationality.